P079 Interleukin-27 regulates the magnitude of the ectopic germinal centre response in a viral-inducible model of sialadenitis. (21st February 2018) - Lucchesi, D; Pontarini, E; Coleby, R; Jones, GW; Hill, DG; Pitzalis, C; Bombardieri, M
Abstract : Introduction: Ectopic lymphoid structures (ELS) are leukocytes aggregates that form in tissues affected by chronic inflammation. In autoimmunity, ELS play an active role in disease progression and are typically associated with aggressive disease. Thus, understanding the mechanisms that trigger ELS formation is of paramount importance for therapeutic targeting of this process. Interleukin-27 (IL-27) is prominently associated with the negative control of adaptive immunity, and in particular in the suppression of Th17-type responses. Objectives: To elucidate the role of IL-27 in the control of lymphoid neogenesis and its functional relationship with aberrant IL-17 production in a murine model of inducible ELS, where the local administration of a replication-deficient adenovirus (AdV) triggers the formation of ectopic germinal centres in salivary glands (SG). Methods: A single administration of AdV was delivered by cannulation directly into the SG of wild-type (WT) and IL-27R-deficient ( Il27ra -/- ) mice. For IL-17A blockade, an anti-mouse IL-17A antibody or IgG control was administered systemically. ELS development and peripheral immune responses were temporally tracked by immuno-histopathology, flow cytometry, and real-time qPCR. Results: AdV cannulation induced an early upregulation of IL-27 and IL-27R in WT mice SG, which was mirrored by an increase in the infiltration of IL-27-producing T, B and NK cells. AdV-challenged Il27ra -/- mice developed exacerbated salivary gland inflammation, and by day-19 post AdV challenge developed larger and more abundant ELS as compared to WT mice. Moreover, Il27ra -/- mice displayed a heightened expression of homeostatic cytokines, chemokines and their corresponding receptors that are required for lymphoid neogenesis (e.g., Cxcl13, Ccl19 and Ltb ). IL-27R-deficient mice also displayed elevated markers of functional germinal centre responses (e.g., activation-induced deaminase, AID). Underpinning the exaggerated development of ELS in Il27ra -/- mice was the preferential expansion of IL-17-producing T helper (Th)17 cells, which was linked to a reduction in the Th1 cell population. This was confirmed using a neutralising antibody to IL-17A, which resulted in a reduction in the size of ELS as determined by immunofluorescence detection of T and B-cell involvement. The inhibition of ELS development by anti-IL-17A treatment was also reflected by the reduced expression of lymphoid chemokines and AID. Notably, the infiltration of IL-22-producing CD4 +cells, a key effector population involved in ELS formation, was also reduced in anti-IL-17-treated Il27ra -/- but not WT mice. Conclusions: Here we show that IL-27 has a non-redundant inhibitory role in the regulation of the magnitude of ectopic germinal centre responses in inflamed SG. In the absence of a regulatory IL-27 signal, an exaggerated Th17 cell response was linked to dysregulated ELS size and activity. These findings provide new insights into the mechanisms governing ELS formation and highlight the role of IL-27 as an endogenous inhibitor of lymphoid neogenesis which could be exploited for therapeutic purposes in autoimmune diseases. Disclosure of interest: None declared